The Effect of Pounching-Ped Variation Training on the Accuracy of Circle Kicks in KONI Palembang Satlat Tarung Derajat Athletes - Alisha, Wieta Devy; Syafaruddin, Syafaruddin; Hartati, Hartati (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The research entitled The Effect of Pounching-Ped variation training on the level of accuracy of circle kicks in Koni Palembang satlat degree fighting athletes was carried out with the aim of finding out the effect of Pounching-Ped variation training on the ability of circle kick accuracy in Palembang Koni Satlat Tarung Derajat athletes. The population of this research was Tarung Derajat satlat Koni Palembang athletes, totaling 22 people. The sample for this research consisted of 22 people. The method used in this research is experimentation. With a One Group PreTest-PostTest design. The treatment in this study was the Pounching-Ped variation exercise with a training frequency of 3 times a week. Based on the results of research and statistical data analysis of the Shapiro Wilk normality test and t test, the results showed that the difference in mean values ​​increased by 4.364 and a significance value of 0.000 (<0.05). Thus, it can be concluded that Pounching-Ped variation training is stated to have an effect on the accuracy of circle kicks in Koni Palembang satlat fighting athletes.